2004
DOI: 10.1097/00002371-200407000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Antigen Loading Strategies of Dendritic Cells for Tumor Immunotherapy

Abstract: Dendritic cells (DCs) loaded with antigens can effectively stimulate host immune responses to syngeneic tumors, but there is considerable controversy as to which forms of antigen-loading are most immunogenic. Here, the authors compared immunotherapeutic reactivities of DCs loaded with a variety of antigen preparations. Because DC maturation stages affect their capacities of antigen processing and presentation, two DC populations were used for the current analysis: in vivo Flt-3 ligand-induced mature DCs and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 29 publications
0
62
0
Order By: Relevance
“…Bone marrow DCs were prepared as previously described (14) by a modification of Inaba and colleagues (15). Briefly, cells harvested from femora and tibiae were depleted of B and T cells by negative selection with mAb-coated magnetic beads (Dynal Biotech).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow DCs were prepared as previously described (14) by a modification of Inaba and colleagues (15). Briefly, cells harvested from femora and tibiae were depleted of B and T cells by negative selection with mAb-coated magnetic beads (Dynal Biotech).…”
Section: Introductionmentioning
confidence: 99%
“…The cell suspensions were then resuspended in conditioned medium and incubated overnight in a 37jC, 5% CO 2 incubator. The adherent cell fraction containing fusion hybrids was harvested and Three days later, mice were vaccinated by the intranodal route as previously described (14). Routinely, 3 Â 105 fusion cells in 10 AL HBSS were delivered to each of 2 superficial inguinal lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that DCs were capable of stimulating T cells to produce IL-10 nonspecifically, and this pattern of production did not influence therapeutic responses. 43 Moreover, it was also demonstrated that IL-10 production could enhance CTL generation. 44,45 In summary, we have demonstrated, using DC/CRCA fusion cells, that (i) freshly isolated metastatic CRCA cells can be used as a fusion partner, thus expanding the source of fusion cells; (ii) both CD4…”
mentioning
confidence: 99%
“…These results suggest that DC/tumour fusion hybrids are stronger stimulators of protective immunity against solid tumours than other antigen-loading strategies using whole tumour cell materials [35]. Furthermore, DC/tumour cell fusion hybrids have been shown to demonstrate superior efficacy for the treatment of murine tumour models than other DC-based vaccination strategies in other studies [39][40][41][42][43]. Parameters that may require further adjustment to maximize the anti-tumour effect of DC/tumour cell fusion hybrids include the DC maturation state, fusion efficiency between DC and tumour cells, and the use of appropriate adjuvants.…”
Section: Dendritic Cell/tumour Fusion Hybrids and Their Utility In Camentioning
confidence: 88%